Collective Leader Efficacy: Developing a Systems Construct to Strengthen Instructional Leadership Teams - DeWitt, Peter; Nelson, Michael (International Journal of Education Policy and Leadership, 2026)
Collective efficacy is a well-established explanatory construct in education, yet research has focused primarily on teachers, leaving the collective efficacy of leadership teams less well-defined and empirically specified. Drawing on social cognitive theory and leadership scholarship, this article conceptualizes collective leader efficacy (CLE)—defined as leadership teams’ shared belief in their collective capability to influence adult and student learning—through three interdependent dimensions: shared understanding (coherence around purpose and priorities), joint work (cross-role inquiry and collaborative problem-solving), and evidence of progress (routines for interpreting whether leadership work is improving system conditions). Findings clarify CLE as a bounded leadership-team construct and foreground testable propositions regarding consistency routines, inquiry structures, and evidence cadence that can guide future measurement development and outcome-linked research.